PERSEPSI PETANI TERHADAP INOVASI TEKNOLOGI PENGELOLAAN TANAMAN TERPADU PADI GOGO DI KABUPATEN SARMI PROVINSI PAPUA - Petrus A Beding (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2015)
This study aims to determine the perception of the application of innovation upland rice integrated crop management at the farm level. The research was conducted from May to October 2015 in the village of Mukti Mawes, District Bonggo, Sarmi. Data collected through a structured interview with guiding questions (questionnaire). Data were analyzed descriptively. The results showed that farmers have a positive perception of technological innovation upland rice integrated crop management. Farmers assume that upland rice integrated crop management profitable, uncomplicated, easy to try, easy to see the result, not bertentangkan with the values of local traditions and in accordance with the needs of the community. Perception level of technological innovation Integrated Crop Management upland rice reached 89.12%. The efforts of priorities that need attention in order to improve farmers' understanding of the management of upland rice farming that is both integrated manner by taking into account several factors: the income of farmers, farm business climate supportive of farmers and extension activities better.